Improving Recruitment and Retention of Pharmacists in a Practice-Based Research Network - Katherine Rotzenberg; Michelle A. Chui (MDPI AG, 2019)
Pharmacy practice-based research networks (PBRNs) are relatively new compared to their primary care forebears, representing a unique set of research challenges. Recruitment and retention of network members are essential to maintaining the integrity of the network and achieving its research goals. Many studies have evaluated recruitment and retention of practitioners to individual studies, while far fewer have reported on recruitment and retention to the network itself. This literature review summarizes current practices for PBRN member recruitment and retention from a pharmacy perspective.